OWNERSHIP STRUCTURE AND AUDIT FEES IN INDONESIA - Agil Novriansa; Asfeni Nurullah; Aryanto Aryanto (JRAK, 2023)
Different types of ownership structures provide distinct corporate monitoring mechanisms, thus affecting the magnitude of company audit fees. This study aims to empirically examine the relationship between ownership structure and audit fees in Indonesia from the agency theory perspective. The sample comprises non-financial companies listed in the Indonesian capital market over 2015-2021. Based on the purposive sampling results, the final number of observations in this research is 931 company-years. This study employs pooled OLS panel data regression with robust standard error. Results indicate that non-executive director ownership, family ownership, financial institution ownership, and non-financial institution ownership are negatively related to audit fees. Additionally, managerial ownership and foreign ownership are positively related to audit fees. However, the study does not find a positive relation between government ownership and audit fees. Overall, the results of this research support the agency theory, with a focus on the assumption of convergence of interest.